Extensive Deep Venous Thrombosis in a Patient with Neurolept Malignant Syndrome despite Being on Prophylaxis - Jerrin C. Mathew; Unnikrishnan Pillai; Alexander Lacasse (Case Reports in Psychiatry)
The risk of venous thromboembolism (VTE) in patients with Neuroleptic malignant syndrome (NMS) and those on antipsychotic medications is well established. We present here a case whereby the patient had NMS and developed extensive deep venous thrombosis (DVT) despite being on standard DVT Prophylaxis. Our case illustrates that empiric intravenous heparin for the initial few days after the onset of NMS may be considered in those with high risk of VTE, as in such patients standard DVT prophylaxis may not be sufficient. To standardize as to which patients with NMS would be at the highest risk of VTE while on standard DVT prophylaxis, the role of a standardized scoring system and a double-blind randomized trial in the future would probably be beneficial.